HOLOCENE SHORELINES AND TECTONIC UPLIFT OF THE ISLAND OF LIPAN (AEOLIAN ARC, SOUTHERN ITALY) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2020)
Two succeeding phases in the evolution of Lipari island have been identified and are discussed in the present paper. At first, eight orders of marine terraces were recognized on the ground of geomorphological, sedimentological and paleontological evidences. The U234/U238 datings of the fossil shells recovered from terraces Ill and V have allowed to set the age of these ancient shorelines. These datings implemented with those from the literature, make the basis for the construction of an uplift/sinking diagram. From this latter it stems that a sinking has occurred approximately during the Eutyrrhenian. The subsequent rise took place at a rate of 0.73-0.33 cm/year,
Keywords: Quaternary stratigraphy; Molluscs; Paleoecology; Tectonic movements.